Computer Analysis of Images and Patterns 14th International Conference, CAIP 2011, Seville, Spain, August 29-31, 2011, Proceedings, Part I - Berciano, Ainhoa; Díaz-Pernil, Daniel; Kropatsch, Walter; Molina-Abril, Helena; Real, Pedro (Image Processing, Computer Vision, Pattern Recognition, and Graphics, 2011)
The two volume set LNCS 6854/6855 constitutes the refereed proceedings of the International Conference on Computer Analysis of Images and Patterns, CAIP 2011,  which took place in Seville, Spain, August 29-31, 2011. The 138 papers presented together with 2 invited talks were carefully reviewed and selected from 286 submissions. The papers are organized in topical section on: motion analysis, image and shape models, segmentation and grouping, shape recovery, kernel methods, medical imaging, structural pattern recognition, Biometrics, image and video processing, calibration; and tracking and stereo vision.